The sources and formation processes of brines from the Lunnan Ordovician paleokarst reservoir, Tarim Basin, northwest China. Issue 3 (11th April 2013) - Chen, J.; Liu, D.; Peng, P.; Yu, C.; Zhang, B.; Xiao, Z.
Abstract The most important petroleum exploration target in the Tarim Basin, northwest China, is the paleokarst reservoir. To understand the source and evolution of brine in this type of reservoir, a total of 37 formation‐water samples were collected from the Middle‐Lower Ordovician paleokarst reservoir in the Lunnan oilfield. The δD‐δ18O correlation and Cl/Br ratios reflect the mixture of two fluids: meteoric water and evaporated seawater. The different degree of mixture divided samples into two groups. Group 1 samples, from deep strata (5150–6667 m.b.s.l.) in the east of the field, with elevated δD (−53.5 to −38.0‰), δ18O values (0.66–5.99‰), and lower Cl/Br ratios (336–478 for Cl/Br, except LN634‐1 and LN631‐1) were formed by evaporation of seawater plus a small contribution from meteoric water. Group 2 samples, from shallow strata (5038–6067 m.b.s.l.), in the west of the field, have contrasting features (−59.6 to −48.5‰ for δD, −0.47 to 2.17‰ for δ18O, and 501 to 871 for Cl/Br), which reflect a mixture of evaporated seawater with a high proportion of meteoric water. Both of the fluid types exchanged oxygen isotope with minerals. The investigation into cation composition reveals that, before entering into the current reservoir, waters suffered albitization of plagioclase; moreover, meteoric water dissolved evaporites and seawater experienced dolomitization. A mixing trend showed by strontium isotopes (0.709801–0.711628) gave further evidence for the mixture of two fluid types. Based on the correlation of geological history with our data, two infiltration models of meteoric waters can be constructed. According to the chemical and isotopic compositions of the waters, an east fluid regime (Group 1) and a west fluid regime (Group 2) have thus been defined. Better understanding of the subsurface fluid movement patterns may be helpful for the local exploration.